Gene Expression of Human Beta-Defensin-3 and Cathelicidin in the Skin of Leprosy Patients, Household Contacts, and Healthy Individuals from Indonesia - Argentina F; Suwarsa O; Gunawan H; Berbudi A (Dove Medical Press, 2023)
Fifa Argentina,1,2 Oki Suwarsa,3 Hendra Gunawan,3 Afiat Berbudi4,5 1Doctoral Program in Medical Science, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 2Department of Dermatology and Venereology, Faculty of Medicine, Universitas Sriwijaya/Mohammad Hoesin General Hospital, Palembang, South Sumatera, Indonesia; 3Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran/Hasan Sadikin General Hospital, Bandung, West Java, Indonesia; 4Department of Biomedical Sciences, Parasitology Division, Faculty of Medicine, Universitas Padjadjaran, Bandung, West Java, Indonesia; 5Research Center for Care and Control of Infectious Disease, Universitas Padjadjaran, Bandung, West Java, IndonesiaCorrespondence: Hendra Gunawan, Department of Dermatology and Venereology, Faculty of Medicine, Universitas Padjadjaran- Dr. Hasan Sadikin General Hospital, Jl. Pasteur No. 38, Bandung, West Java, 40161, Indonesia, Tel/Fax +62222032426, Email h.gunawan2016@unpad.ac.idBackground: Leprosy, a chronic infectious peripheral neuropathy, is caused by Mycobacterium leprae. This bacterium produces triacylated lipopeptides that can induce the immune system via the Toll-like receptor 2/1 (TLR 2/1) complex. Activation of TLR 2/1 produces proinflammatory cytokines and antimicrobial peptides (AMPs), including human beta-defensin-3 (HBD-3) and cathelicidin.Purpose: To analyze differences in gene expression of HBD-3 and cathelicidin in the skin of leprosy patients, household contacts, and healthy individuals.Patients and Methods: An analytic observational study was conducted at the Outpatient Clinic of Dermatology and Venereology of Dr Mohammad Hoesin General Hospital, Palembang, Indonesia, from January 2021 to June 2022. In each group of 18 subjects, 72 samples were collected, including skin lesion in leprosy patients, normal skin in leprosy patients, household contacts, and healthy individuals. A comparison of HBD-3 and cathelicidin gene expression between the four groups was analyzed using Pearson Chi Square, Kruskal-Wallis, and Mann-Whitney Test.Results: The median value of HBD-3 gene expression on skin lesion in leprosy patients was 260.61 (0.19- 3734.10); normal skin in leprosy patients was 1.91 (0.01- 151.17); household contacts skin was 7.93 (0.27- 121.10); and healthy individuals' skin was 1.00 (1.00- 1.00) is highly significant difference (p < 0.0001). The median value of cathelicidin gene expression on skin lesion in leprosy patients was 38.72 (0.28- 1852.17); normal skin in leprosy patients was 0.48 (0.01- 15.83); household contacts skin was 9.8 (0.04- 128.0); and healthy individual skin was 1.00 (1.00- 1.00), also highly significant difference (p < 0.0001).Conclusion: Gene expression of HBD-3 and cathelicidin increased in skin lesions of leprosy patients and household contacts.Keywords: cathelicidin, HBD-3, household contacts, leprosy